Evolution and circulation of Yersinia pestis in the Northern Caspian and Northern Aral Sea regions in the 20th-21st centuries. - Galina A Eroshenko; Nikolay V Popov; Zhanna V Al'khova; Lyubov M Kukleva; Alina N Balykova; Nadezhda S Chervyakova; Ekaterina A Naryshkina; Vladimir V Kutyrev (PLoS ONE, 2021)
According to the whole genome SNP analysis of 38 Yersinia pestis strains isolated in the foci of the Northern Caspian and Northern Aral Sea regions in the 20th-early 21st centuries, between 1912 and 2015, the spatial and temporal structure of the 2.MED population of a medieval biovar in this region was determined. A phylogenetic branch 2.MED4 was identified which preceded the 2.MED1 branch that diverged later. 2.MED1 strains became the etiological agent of high-mortality plague outbreaks that occurred in the Northern Caspian region at the beginning of the 20th century. Later in the 20th century, the 2.MED1 branch became widespread in the Caspian Sea region, Caucasus, and vast areas of Central Asia. Based on the data of phylogenetic analysis, as well as epidemiological and epizootiological data, we reconstructed the paths of spread of the 2.MED1 branch in the Northern Caspian Sea region and in the Northern subzone of the Central Asian deserts. It is shown, that the reason for the activation of plague foci in the Northern Caspian region in the second half of the 20th century after a long inter-epizootic period caused by cyclical climate warming was the return of 2.MED1 from the foci of the Northern Aral Sea region. This led to the formation of stable plague foci in the Northern Caspian Sea region and Pre-Caucasus, which manifested epizootic activity in the second half of the 20th and early 21st centuries.